Current rates of Helicobacter pylori infection and antibiotic resistance in the eastern coast of China: a single center study - Chen, Hui-Jin; Si, Yu-Ting; Luan, Luan; Lai, Jin-Xin; Wang, Ji-Liang; Tang, Yu-Rong; Wang, Liang (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHelicobacter pylori (H. pylori), linked to gastric cancer, lacks regional data on infection rates, resistance, and risks in Dongying, China.MethodsA pilot study (N = 314) using non-invasive string tests and qPCR assessed H. pylori prevalence and antibiotic resistance. Logistic regression identified risk factors from survey data.ResultsThe H. pylori infection rate in Dongying was 24.84% (78/314, 95% CI: 20.06%-29.62%). Of the infected individuals, 60.25% (47/78, 95% CI: 49.40%-71.12%) and 46.15% (36/78, 95% CI: 35.09%-57.22%) showed resistance to clarithromycin and levofloxacin, respectively.ConclusionsThis pilot study provides preliminary data with valuable insights for preventing the transmission of H. pylori infection among the urban population in the East Coast region of China and offers guidance for the personalized treatment of drug-resistant H. pylori infections.